A preliminary study of rural women entrepreneurs: Characteristics and business success factors - Abdullah, Norehan; Hassan, Kalthum; Yusof, Rohana (2014)
This paper aims to identify a demo-socio-economic profile of rural women entrepreneurs and investigate the elements of how cultural values, Islamic values, social and environment, individual beliefs, and opportunities/infrastructure have influence on the successful of rural business women.In this preliminary study, a total of 36 respondents in northern area of Kedah were interviewed.This study found most of the entrepreneurs are married and have some previous working experience.The result shows that almost 80 per cent of respondents believe in religion, work hard, and always thankful to God. They highlighted the importance of exposure to entrepreneurships since childhood, and keeping good manners as the most important factors in influencing the success of the business.In terms of Islamic practice, a total of 80.6 per cent agreed that the business must be ‘halal’ and trustworthy is a must in each transaction involved.This study further discovers that the biggest challenge is to balance the time between family and business.